Radiological Tenckhoff catheter insertion for peritoneal dialysis: A cost‐effective approach. Issue 2 (1st August 2017) - Lee, James; Mott, Nigel; Mahmood, Usman; Clouston, John; Summers, Kara; Nicholas, Pauline; Gois, Pedro Henrique França; Ranganathan, Dwarakanathan
Abstract: Introduction: Radiological insertion of Tenckhoff catheters can be an alternative option for peritoneal dialysis access creation, as compared to surgical catheter insertion. This study will review the outcomes and complications of radiological Tenckhoff catheter insertion in a metropolitan renal service and compare costs between surgical and radiological insertion. Methods: Data were collected prospectively for all patients who had a Tenckhoff catheter insertion for peritoneal dialysis (PD) under radiological guidance at our hospital from May 2014 to November 2016. The type of catheter used and complications, including peri‐catheter leak, exit site infection and peritonitis were reviewed. Follow‐up data were also collected at points 3, 6 and 12 months from catheter insertion. Costing data were obtained from Queensland Health Electronic Reporting System (QHERS) data, average staff salaries and consumable contract price lists. Results: In the 30‐month evaluation period, 70 catheters were inserted. Two patients had an unsuccessful procedure due to the presence of abdominal adhesions. Seven patients had an episode of peri‐catheter leak, and four patients had an exit site infection following catheter insertion. Peritonitis was observed in nine patients during the study period. The majority of patients (90%) remained on peritoneal dialysis at 3‐month follow‐up. The average costs of surgical and radiological insertion were noted to be AUD$7788.34 and AUD$1597.35, respectively. Conclusion: Radiological Tenckhoff catheter insertion for peritoneal dialysis appears to be an attractive and cost‐effective option given less waiting periods for the procedure, the relatively low cost of insertion and comparable rates of complications.